Effects of lifting task parameters on body kinematics - Tan, Yuwei. (2013)
Nowadays, with aging population problem arising in Singapore, it is critical to understand how manual material handing (MMH) tasks is affecting the human body especially when there is a raised of aging people in the labour force. It is also usually assumed that MMH have direct association with low back pain (LBP). Even through with continual improvement of technology and machine, many would still manually do tasks such as lifting objects. Thus, it is important to understand what the reaction on the joint of the body is and how the musculoskeletal system behaves during MMH tasks such as lifting [1].